2010
DOI: 10.1002/cphc.201000104
|View full text |Cite
|
Sign up to set email alerts
|

Water Adsorption on Platinum Dioxide and Dioxygen Complex: Matrix Isolation Infrared Spectroscopic and Theoretical Study of Three PtO2–H2O Complexes

Abstract: The interactions of water molecule with platinum dioxygen complex and dioxide molecule are investigated by means of matrix isolation infrared spectroscopy and density functional calculations. The platinum atoms reacted with dioxygen to form the previously reported Pt(O(2)) complex. The Pt(O(2)) complex reacted with water molecule to give the Pt(O(2))-H(2)O complex, which was characterized to involve hydrogen bonding between one O atom of Pt(O(2)) and one H atom of H(2)O (structure A). Upon visible light irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…The presence of adsorbed OH-H 2 O complexes on oxidized noble metals has been reported experimentally and through DFT analysis in several publications. [56][57][58][59] Kan et al 56 studied the adsorption of water on a PdO(101) thin film using temperature-programmed desorption measurements and DFT calculations. They found that water desorbs from a multilayer which appears to be stabilized by direct interactions with the oxidized surface and that the HO-H 2 O complex is highly favored at low water coverages along the coordinatively unsaturated Pd atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of adsorbed OH-H 2 O complexes on oxidized noble metals has been reported experimentally and through DFT analysis in several publications. [56][57][58][59] Kan et al 56 studied the adsorption of water on a PdO(101) thin film using temperature-programmed desorption measurements and DFT calculations. They found that water desorbs from a multilayer which appears to be stabilized by direct interactions with the oxidized surface and that the HO-H 2 O complex is highly favored at low water coverages along the coordinatively unsaturated Pd atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Another explanation for the high O/Pt ratio could be the formation of PtO 2 ÁH 2 O (Pt in oxidation state 4). [23] The incorporation of H 2 O in the matrix can be related to the H 2 O formed as a reaction product from the combustion of the precursor ligands, which is well known for Pt ALD. [9,24] In the work of Hämäläinen et al an O/Pt ratio between 1.09 and 1.66 has been reported.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Additionally Xu has studied the interaction of Cu, Ag, and Au atoms with O 2 and CO, and different molecules have been characterized: (O 2 )­Cu­(CO) 1,2 , OO­(M)­CO (M = Cu, Ag), OCAuO 2 CO, and OAuCO . Finally, Zhou has studied the interactions of water molecules with platinum dioxygen complex and dioxide molecule, and three PtO 2 –H 2 O complexes were identified . In another work, the reactions of early lanthanide metal atoms (Ce, Pr, and Nd) with carbon monoxide and nitric oxide have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…10 Finally, Zhou has studied the interactions of water molecules with platinum dioxygen complex and dioxide molecule, and three PtO 2 −H 2 O complexes were identified. 11 In another work, the reactions of early lanthanide metal atoms (Ce, Pr, and Nd) with carbon monoxide and nitric oxide have been investigated. The results show that the reactions proceed with the initial formation of a linear inserted NLnO molecule, which subsequently reacts with CO to form the NLnO(CO) complex.…”
Section: ■ Introductionmentioning
confidence: 99%